The Optimization of Shell and Tube Condenser Cooling System on a 5-Liter Distillation Apparatus Using a Water Jacket with Thermoelectric - I Made Sudana; I Wayan Marlon Managi (Green Publisher Indonesia, 2026)
Background: In small-scale alcohol distillation, the efficiency of the condenser is critical for product quality and yield. A common problem is the rise in condenser temperature during operation, which diminishes vapor condensation efficiency and results in low alcohol concentration in the distillate. Objective: This research aims to optimize the performance of a shell-and-tube condenser in a 5-liter distillation apparatus by integrating a water jacket system equipped with a thermoelectric (Peltier) cooler. Methods: An experimental approach was employed, comparing the apparatus's performance before and after modification. Key parameters measured included inlet vapor temperature, inlet and outlet cooling water temperatures of the condenser, process duration, and the alcohol concentration of sequential distillate fractions. Results: The findings demonstrate that the thermoelectric water jacket significantly reduced and stabilized the condenser's outlet water temperature throughout the operation. The time to obtain the first distillate decreased from 23 to 16 minutes. The alcohol concentration of the initial fraction increased from 40% to 50%, and the total processing time for the same 5-liter batch was reduced from 55 to 35 minutes. Conclusion: The integration of a thermoelectric water jacket substantially enhances heat transfer and alcohol vapor condensation efficiency. This modification proves to be an effective strategy for improving the thermal performance and product quality of small-scale distillation equipment.